2023
DOI: 10.1186/s12885-023-10628-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation analysis of host genes in cervical intraepithelial neoplasia and cervical cancers on histological cervical specimens

Abstract: Background DNA methylation is an essential factor in the progression of cervical intraepithelial neoplasia (CIN) to cervical cancer. The aim was to investigate the diagnostic value provided by methylation biomarkers of six tumor suppressor genes (ASTN1, DLX1, ITGA4, RXFP3, SOX17 and ZNF671) for cervical precancerous lesions and cervical cancer. Methods The histological cervical specimens of 396 cases including 93 CIN1, 99 CIN2, 93 CIN3 and 111 cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…However, this strategy still has a relatively high rate of unnecessary colposcopy [31]. On the other hand, p16/Ki67 dual staining [32], gene methylation detection [33], and E6 protein detection have shown promise in reducing unnecessary colposcopic referrals. Given the advantages of objective and highthroughput gene methylation detection, coupled with the rich biological information contained in gene methylation results, this study constructed three machine learning models based on multistep screening of multigene methylation information.…”
Section: Discussionmentioning
confidence: 99%
“…However, this strategy still has a relatively high rate of unnecessary colposcopy [31]. On the other hand, p16/Ki67 dual staining [32], gene methylation detection [33], and E6 protein detection have shown promise in reducing unnecessary colposcopic referrals. Given the advantages of objective and highthroughput gene methylation detection, coupled with the rich biological information contained in gene methylation results, this study constructed three machine learning models based on multistep screening of multigene methylation information.…”
Section: Discussionmentioning
confidence: 99%
“…Others have tested methylated gene markers alone, or combined with HPV-testing and cytology to determine whether the three-pronged approach would improve detection and risk stratification of low-grade lesions [ 26 ]. A number of commercial methylation tests have used single-host gene methylation of POU4F3 (sensitivity 74% and specificity 89%) [ 48 ], PAX1 (sensitivity 78%, and specificity 92%) [ 49 ], or panels of two, PAX1/ZNF582 (sensitivity 78.85% and specificity 73.55%) [ 50 ] to six markers [ 17 19 , 51 ]. A number of studies have used the 6-marker GynTect® assay.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have used the 6-marker GynTect® assay. Sensitivity for CIN3 detection in these studies ranged from 64 to 91% and specificity ranged from 42 to 95% [ 17 19 , 51 ]. The S5-classifier consists of markers of HPV gene methylation combined with a host gene marker, EPB41L3, showed a high sensitivity of 93.2% but a low specificity of 41.8% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 However, the overall number of clinical observational studies on DNA gene methylation is relatively small and most of them mention the use of a six-gene kit (ASTN1, DLX1, ITGA4, RXFP3, SOX17 and ZNF671) for combined methylation detection, which deserves our special attention. For example, Shi et al 17 found that it showed excellent diagnostic efficiency in screening samples with CIN2+ and above in the diagnostic value of methylation biomarkers using this kit for cervical precancerous lesions and cervical cancer. Zhang et al 18 found that using methylation screening can reduce the referral rate of colposcopy by 67.2%, with a sensitivity and specificity of 83.0% and 69.9% for detecting CIN2+.…”
Section: Introductionmentioning
confidence: 99%